Thermal insulation fiber and textile made of same

By coating the thermal insulation coating of modified aerogel and antibacterial microcapsule system on the fiber surface, using silica aerogel and nanosilver particles, the problem of insufficient fiber insulation performance is solved, and efficient insulation and inhibition is achieved Bacterial effect.

CN119243478APending Publication Date: 2025-01-03ALLIS EDUCATIONAL EQUIP TECH (SUZHOU) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411379228.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The insulation performance of existing fibers is difficult to meet the market's demand for high efficiency and energy saving, and cannot effectively slow down the dissipation and transmission of heat.

Method used

The thermal insulation coating with a modified aerogel system and an antibacterial microcapsule system is applied to the fiber surface, and the insulation and antibacterial properties of the fiber are improved by using silica aerogel materials and nanosilver particles.

Benefits of technology

It significantly improves the thermal insulation and antibacterial properties of the fiber, and achieves good thermal stability and long-term antibacterial effects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005069474040000081
    Figure BDA0005069474040000081
  • Figure BDA0005069474040000091
    Figure BDA0005069474040000091
Patent Text Reader

Abstract

The invention relates to a heat preservation and insulation fiber and a textile made of the fiber, the heat preservation and insulation fiber comprises a fiber body and a heat insulation coating, the heat insulation coating is obtained by coating the surface of the fiber body with a heat insulation coating, and the heat insulation coating comprises a modified aerogel system, a bacteriostatic microcapsule system, waterborne polyurethane and a dispersing agent; the modified aerogel system comprises a silicon dioxide aerogel material and a silane coupling agent. The method has the effect of improving the thermal insulation performance of the fiber.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of fibers, and in particular to a thermal insulation fiber and a textile made of the fiber. Background Art

[0002] Fiber refers to a substance composed of continuous or discontinuous filaments, which is widely used in the textile industry. It can be made into fabrics, which can then be made into clothing and used in various fields.

[0003] Thermal insulation is a scientific and efficient energy-saving technical measure that can slow down the speed of heat dissipation and conduction. As the market's requirements for fibers are getting higher and higher, the requirements for thermal insulation effects are also getting higher and higher; however, the current thermal insulation performance of fibers is difficult to meet the thermal insulation needs, so it is necessary to provide a fiber that further improves the thermal insulation performance. Summary of the invention

[0004] In order to improve the thermal insulation performance of fibers, the present application provides a thermal insulation fiber and a textile made from the fiber.

[0005] The present application provides a thermal insulation fiber and a textile made of the fiber using the following technical solutions: In the first aspect, the present application provides a thermal insulation fiber, which adopts the following technical solution: A thermal insulation fiber comprises a fiber body and a thermal insulation coating, wherein the thermal insulation coating is obtained by coating the thermal insulation coating on the surface of the fiber body, the thermal insulation coating comprises a modified aerogel system, an antibacterial microcapsule system, an aqueous polyurethane and a dispersant; the modified aerogel system comprises a silica aerogel material and a silane coupling agent.

[0006] By adopting the above technical scheme, a layer of thermal insulation coating is coated on the surface of the fiber body, so that a layer of thermal insulation coating is formed on the surface of the fiber body. The modified aerogel system in the thermal insulation coating is prepared from silica aerogel material and a silane coupling agent. The silica aerogel material is an excellent thermal insulation material with high porosity and surface area, low density and excellent thermal conductivity. After being attached to the surface of the fiber body, the fiber body has good thermal insulation performance. After the silica aerogel material is modified with silica, the silica aerogel material has good dispersion performance, which further improves the stability of the thermal insulation coating.

[0007] Preferably, the silica aerogel material is prepared by the following method: Hexadecyltrimethylammonium bromide is mixed with water, and then methyltrimethoxysilane is added, and the mixture is stirred until the system is formed to obtain an oil-in-water emulsion. After hydrolysis, dimethyldimethoxysilane is added to continue hydrolysis to obtain a dispersion. Span-80 is added to n-hexane, and the above dispersion is added to obtain a mixed solution. The mixed solution is stirred to condense a gel, and the gel is separated after filtration, washed, immersed in the mixed solution for aging, and then filtered and dried, and ground to obtain a silica aerogel material.

[0008] By adopting the above technical scheme, hexadecyltrimethylammonium bromide is used as an emulsifier, methyltrimethoxysilane and dimethyldimethyldimethoxysilane are used as precursors, and after being hydrolyzed into silanols, a silica aerogel material is prepared through condensation. After hydrolysis, dimethyldimethoxysilane enters the gel skeleton structure through a condensation process and can occupy a larger space steric hindrance, thereby reducing the pore size of the aerogel micropores and making the aerogel particle size uniform. In addition, the introduction of dimethyldimethoxysilane promotes the hydrophobicity of the silica aerogel microspheres after hydrolysis. At the same time, the increase in the methyl content further improves the overall thermal stability of the system.

[0009] Preferably, the mass ratio of methyltrimethoxysilane to dimethyldimethoxysilane is (3.4-3.8):1.

[0010] By adopting the above technical solution, preferably the mass ratio of methyltrimethoxysilane to dimethyldimethoxysilane is within the above range, the stability of the prepared silica aerogel material can be further improved.

[0011] Preferably, the modified aerogel system is prepared by the following method: After gamma-aminopropyltriethoxysilane, ethanol and water are mixed, a silane coupling agent solution is obtained by ultrasonic treatment, a silica aerogel material is added into the silane coupling agent solution and ultrasonic treatment is performed, and a modified aerogel system is obtained after drying and grinding.

[0012] Preferably, the silane coupling agent includes γ-aminopropyltriethoxysilane.

[0013] By adopting the above technical scheme, γ-aminopropyltriethoxysilane can combine with organic matter and inorganic matter after being exposed to water. After being compounded with the silica aerogel system, the compatibility and dispersibility of the silica aerogel can be improved, the occurrence of agglomeration of the silica aerogel can be reduced, and the combination with the fiber body can be tighter, thereby improving the overall stability of the thermal insulation coating.

[0014] Preferably, the mass ratio between the silica aerogel material and the silane coupling agent is 1:(0.02-0.04).

[0015] By adopting the above technical solution, the mass ratio between the silica aerogel material and the silane coupling agent is preferably within the above range, which can further improve the overall comprehensive performance of the prepared silica aerogel.

[0016] Preferably, the antibacterial microcapsule system comprises nanosilver particles, citronella essential oil and an emulsifier.

[0017] By adopting the above technical scheme, citronella essential oil is a natural antioxidant essential oil with ingredients such as geraniol and citronellol, which can have a significant antibacterial effect, but it is volatile and has poor stability in the air. Nanosilver particles are a traditional and effective antibacterial agent with good antibacterial properties. Citronella essential oil is used as a profile and nanosilver particles are used as a carrier of a shell material to prepare antibacterial microcapsules, so that the nanosilver particles and citronella essential oil can synergistically inhibit each other, and can effectively improve the overall antibacterial performance and chemical stability of the system. After being attached to the fiber body, the limit has good antibacterial performance and thermal stability.

[0018] Preferably, the antibacterial microcapsule system is prepared by the following method: The nanosilver particles are mixed with water, and a nanosilver ion suspension is obtained after ultrasound. The nanosilver particle suspension is mixed with an emulsifier to obtain a nanosilver particle mixture. Citronella essential oil, methyl methacrylate, ethoxylated trimethylolpropane triacrylate, and azobisisobutyronitrile are mixed to obtain an oil phase. The oil phase is mixed with the nanosilver particle mixture and stirred. The temperature is raised and the stirring is maintained for polymerization reaction for 8 hours to obtain antibacterial microcapsules.

[0019] By adopting the above technical scheme, the emulsifier is combined with the nano silver particles to obtain water-based, and then compounded with the oil phase to obtain a stable water-in-oil emulsion, and then the free radicals initiate a polymerization reaction, the monomers are polymerized into macromolecules, and then move to the interface, and at the same time, the silver particles in the surfactant at the oil-water interface are adsorbed on the capsule wall due to the surface size effect, and together form a capsule wall to cover the citronella oil, and obtain an antibacterial microcapsule system, so that the citronella oil can be protected, thereby improving the overall activity of the citronella oil and achieving a long-lasting antibacterial effect.

[0020] Preferably, the mass ratio of the citronella essential oil, the emulsifier and the nano-silver particles is (1.2-1.6):1:0.6.

[0021] By adopting the above technical solution, the mass ratio of citronella essential oil, emulsifier and nano-silver particles is preferably within the above range, which can further improve the overall stability of the prepared antibacterial microcapsules.

[0022] In a second aspect, the present application provides a textile made of thermal insulation fibers, which adopts the following technical solution: A textile made of thermal insulation fiber is prepared from the thermal insulation fiber.

[0023] By adopting the above technical solution, the textiles prepared from the thermal insulation fiber of the present application have good thermal insulation performance, and the textiles also have good antibacterial properties.

[0024] In summary, the present application includes at least one of the following beneficial technical effects: 1. A layer of thermal insulation coating is coated on the surface of the fiber body, so that a layer of thermal insulation coating is formed on the surface of the fiber body. The silica aerogel material in the thermal insulation coating has high porosity and surface area, and has good thermal insulation performance. After being coated on the surface of the fiber body, the fiber body has good thermal insulation performance; 2. Hexadecyltrimethylammonium bromide is used as an emulsifier, methyltrimethoxysilane and dimethyldimethyldimethoxysilane are used as precursors, and after hydrolysis into silanol, a silica aerogel material is prepared through condensation. After hydrolysis, dimethyldimethoxysilane enters the gel skeleton structure through a condensation process, and can occupy a larger space steric hindrance, thereby reducing the pore size of the aerogel micropores and making the aerogel particle size uniform. In addition, the introduction of dimethyldimethoxysilane after hydrolysis promotes the hydrophobicity of the silica aerogel microspheres. At the same time, the increase in the methyl content further improves the overall thermal stability of the system. 3. The emulsifier is combined with the nano-silver particles to obtain water-based, and then compounded with the oil phase to obtain a stable water-in-oil emulsion. Then the free radicals initiate a polymerization reaction, the monomers polymerize into macromolecules, and then move to the interface. At the same time, the silver particles in the surfactant at the oil-water interface are adsorbed on the capsule wall due to the surface size effect, and together form a capsule wall to cover the citronella oil, and obtain an antibacterial microcapsule system, so that the citronella oil can be protected, thereby improving the overall activity of the citronella oil. After combining with the fiber body, it has a long-term synergistic antibacterial effect, thereby improving the antibacterial performance of the fiber body. DETAILED DESCRIPTION

[0025] The present application is further described in detail below with reference to the embodiments: Description of raw materials: All raw materials in the examples are commercially available; the emulsifier in the antibacterial microcapsules is hexadecyltrimethylammonium bromide (CAS No.: 57-09-0); the dispersant in the thermal insulation coating is ethoxylated-C12-18-alcohol (CAS No.: 68213-23-0), and the fiber bodies used in the examples of this application are all polyester fibers.

[0026] Example 1 Preparation of antibacterial microcapsules: 8 g of polyvinyl pyrrolidone (CAS No.: 9003-39-8) was mixed with 40 g of deionized water to obtain a polyvinyl pyrrolidone solution. 2 mL of ammonia water, 200 mL of ethylene glycol, 20 mL of silver nitrate and 200 mL of water were mixed to obtain a silver nitrate solution. The polyvinyl pyrrolidone solution and the silver nitrate solution were mixed, and the mixture was heated to 120° C. and reacted for 4 h. After the reaction, the mixture was cooled to 25° C. and washed by centrifugation with ethanol. The mixture was dried at 80° C. for 8 h to obtain nanosilver particles. 5.14 g of nanosilver particles were mixed with 150 mL of deionized water, and a nanosilver ion suspension was obtained after ultrasonic treatment. The nanosilver particle suspension was mixed with 8.57 g of an emulsifier. After that, a nanosilver particle mixture was obtained, and 16.29 g of citronella essential oil (CAS No.: 73049-78-2), 1.62 g of methyl methacrylate (CAS No.: 80-62-6), 1.23 g of ethoxylated trimethylolpropane triacrylate (CAS No.: 28961-43-5), and 0.25 g of azobisisobutyronitrile (CAS No.: 78-67-1) were mixed to obtain an oil phase. After the oil phase was mixed with the nanosilver particle mixture, it was stirred at a speed of 2600 r / min for 30 min, and then under a nitrogen atmosphere, the temperature was raised to 78°C, and the stirring polymerization reaction was maintained at a speed of 300 r / min for 8 hours to obtain antibacterial microcapsules.

[0027] Preparation of silica aerogel material: Dissolve 0.2 g of hexadecyltrimethylammonium bromide in 40 g of deionized water, adjust the pH value of the system to 3 with 0.2 g of acetic acid, add 30.91 g of methyltrimethoxysilane (CAS No.: 185-55-3), stir at 600 r / min until the system forms an oil-in-water emulsion, hydrolyze for 15 min, then add 9.09 g of dimethyldimethoxysilane (CAS No.: 1112-39-6) and continue hydrolyzing for 15 min. Then, 2 mL of 0.5 mol / L ammonia water was used to adjust the pH value of the system to 8 to obtain a dispersion; 0.8 g of Span-80 was added to 30 g of n-hexane, and the above dispersion was added to obtain a mixed solution, the mixed solution was stirred at a speed of 800 r / min to condense the gel for 10 minutes, the gel was separated after filtration, washed with anhydrous ethanol, immersed in the mixed solution for aging for 3 hours, then filtered, dried in an oven at 80°C for 6 hours, and ground to obtain a silica aerogel material.

[0028] Preparation of modified aerogel system: 0.6 g of γ-aminopropyltriethoxysilane (CAS No.: 919-30-2), 60 g of ethanol and 120 g of deionized water were mixed, and ultrasonicated for 30 minutes to obtain a silane coupling agent solution. 30 g of silica aerogel material was added to the silane coupling agent solution, ultrasonicated for 30 minutes, dried in a forced air drying oven at 120° C. for 6 hours, and ground to obtain a modified aerogel system.

[0029] Preparation of thermal insulation coating: 220 g of waterborne polyurethane, 13 g of modified aerogel system, 18 g of antibacterial microcapsule system and 2 g of dispersant were mixed, and stirred at a speed of 400 r / min for 15 min to obtain a thermal insulation coating.

[0030] Preparation of thermal insulation fibers: The fiber body was immersed in the thermal insulation coating, heated to 40°C and allowed to stand for 20 minutes to allow the thermal insulation coating to fully adhere to the surface of the fiber body. The fiber body was then separated and dried in a drying oven at 50°C for 3 hours to obtain the thermal insulation fiber.

[0031] Preparing textiles: The thermal insulation fibers are woven to prepare textiles.

[0032] Example 2 Preparation of antibacterial microcapsules: 8 g of polyvinyl pyrrolidone was mixed with 40 g of deionized water to obtain a polyvinyl pyrrolidone solution, 2 mL of ammonia water, 200 mL of ethylene glycol, 20 mL of silver nitrate and 200 mL of water were mixed to obtain a silver nitrate solution, the polyvinyl pyrrolidone solution and the silver nitrate solution were mixed, heated to 120° C. for reaction for 4 h, cooled to 25° C. after the reaction, washed by centrifugation with ethanol, and dried at 80° C. for 8 h to obtain nanosilver particles; 4.61 g of nanosilver particles was mixed with 150 mL of deionized water, and nanosilver ion suspension was obtained after ultrasonication. The nanosilver particle suspension was prepared by mixing 7.69 g of an emulsifier to obtain a nanosilver particle mixture, 17.7 g of citronella essential oil, 1.62 g of methyl methacrylate, 1.23 g of ethoxylated trimethylolpropane triacrylate and 0.25 g of azobisisobutyronitrile were mixed to obtain an oil phase, the oil phase was mixed with the nanosilver particle mixture, and the mixture was stirred at a speed of 2600 r / min for 30 min, and then heated to 78° C. under a nitrogen atmosphere, and stirred at a speed of 300 r / min for polymerization reaction for 8 h to obtain antibacterial microcapsules.

[0033] Preparation of silica aerogel material: 0.2 g of hexadecyltrimethylammonium bromide was dissolved in 40 g of deionized water, 0.2 g of acetic acid was used to adjust the pH value of the system to 3, 31.67 g of methyltrimethoxysilane was added, and the system was stirred at a speed of 600 r / min until an oil-in-water emulsion was formed. After hydrolysis for 15 min, 8.33 g of dimethyldimethoxysilane was added to continue hydrolysis for 15 min, and then 2 mL of 0.5 mol / L ammonia water was used to adjust the pH value of the system to 8 to obtain a dispersion; 0.8 g of Span-80 was added to 30 g of n-hexane, and the above dispersion was added to obtain a mixed solution. The mixed solution was stirred at a speed of 800 r / min for 10 min to condense the gel, and the gel was separated after filtration. After washing with anhydrous ethanol, it was immersed in the mixed solution for aging for 3 h, then filtered, dried in an oven at 80°C for 6 h, and ground to obtain a silica aerogel material.

[0034] Preparation of modified aerogel system: 1.2 g of γ-aminopropyltriethoxysilane, 60 g of ethanol and 120 g of deionized water were mixed, and ultrasonicated for 30 min to obtain a silane coupling agent solution. 30 g of silica aerogel material was added to the silane coupling agent solution, ultrasonicated for 30 min, dried in a forced air drying oven at 120° C. for 6 h, and ground to obtain a modified aerogel system.

[0035] Preparation of thermal insulation coating: 260 g of waterborne polyurethane, 15 g of modified aerogel system, 22 g of antibacterial microcapsule system and 3 g of dispersant were mixed, and stirred at a speed of 400 r / min for 15 min to obtain a thermal insulation coating.

[0036] Preparation of thermal insulation fibers: The fiber body was immersed in the thermal insulation coating, heated to 40°C and allowed to stand for 20 minutes to allow the thermal insulation coating to fully adhere to the surface of the fiber body. The fiber body was then separated and dried in a drying oven at 50°C for 3 hours to obtain the thermal insulation fiber.

[0037] Preparing textiles: The thermal insulation fibers are woven to prepare textiles.

[0038] Example 3 Preparation of antibacterial microcapsules: 8 g of polyvinyl pyrrolidone was mixed with 40 g of deionized water to obtain a polyvinyl pyrrolidone solution, 2 mL of ammonia water, 200 mL of ethylene glycol, 20 mL of silver nitrate and 200 mL of water were mixed to obtain a silver nitrate solution, the polyvinyl pyrrolidone solution and the silver nitrate solution were mixed, heated to 120° C. for reaction for 4 h, cooled to 25° C. after the reaction, washed by centrifugation with ethanol, and dried at 80° C. for 8 h to obtain nanosilver particles; 4.87 g of nanosilver particles were mixed with 150 mL of deionized water, and nanosilver ion suspension was obtained after ultrasonication. The nanosilver particle suspension was prepared by mixing the nanosilver particle suspension with 8.11 g of an emulsifier to obtain a nanosilver particle mixture, 17.02 g of citronella essential oil, 1.62 g of methyl methacrylate, 1.23 g of ethoxylated trimethylolpropane triacrylate and 0.25 g of azobisisobutyronitrile were mixed to obtain an oil phase, the oil phase was mixed with the nanosilver particle mixture, and the mixture was stirred at a speed of 2600 r / min for 30 min, and then heated to 78° C. under a nitrogen atmosphere, and stirred at a speed of 300 r / min for polymerization reaction for 8 h to obtain antibacterial microcapsules.

[0039] Preparation of silica aerogel material: 0.2 g of hexadecyltrimethylammonium bromide was dissolved in 40 g of deionized water, 0.2 g of acetic acid was used to adjust the pH value of the system to 3, 31.31 g of methyltrimethoxysilane was added, and the system was stirred at a speed of 600 r / min until an oil-in-water emulsion was formed. After hydrolysis for 15 min, 8.69 g of dimethyldimethoxysilane was added to continue hydrolysis for 15 min, and then 2 mL of 0.5 mol / L ammonia water was used to adjust the pH value of the system to 8 to obtain a dispersion; 0.8 g of Span-80 was added to 30 g of n-hexane, and the above dispersion was added to obtain a mixed solution. The mixed solution was stirred at a speed of 800 r / min for 10 min to condense the gel, and the gel was separated after filtration. After washing with anhydrous ethanol, it was immersed in the mixed solution for aging for 3 h, then filtered, dried in an oven at 80°C for 6 h, and ground to obtain a silica aerogel material.

[0040] Preparation of modified aerogel system: 0.9 g of γ-aminopropyltriethoxysilane, 60 g of ethanol and 120 g of deionized water were mixed, and ultrasonicated for 30 min to obtain a silane coupling agent solution. 30 g of silica aerogel material was added to the silane coupling agent solution, ultrasonicated for 30 min, dried in a forced air drying oven at 120° C. for 6 h, and ground to obtain a modified aerogel system.

[0041] Preparation of thermal insulation coating: 240 g of waterborne polyurethane, 14 g of modified aerogel system, 20 g of antibacterial microcapsule system and 2.5 g of dispersant were mixed, and stirred at a speed of 400 r / min for 15 min to obtain a thermal insulation coating.

[0042] Preparation of thermal insulation fibers: The fiber body was immersed in the thermal insulation coating, heated to 40°C and allowed to stand for 20 minutes to allow the thermal insulation coating to fully adhere to the surface of the fiber body. The fiber body was then separated and dried in a drying oven at 50°C for 3 hours to obtain the thermal insulation fiber.

[0043] Preparing textiles: The thermal insulation fibers are woven to prepare textiles.

[0044] Example 4 Example 4 is based on Example 3. The difference between Example 4 and Example 3 is that in Example 4, when preparing the antibacterial microcapsules, 15.46 g of citronella essential oil, 9.09 g of emulsifier and 5.45 g of nano silver particles are used.

[0045] Example 5 Example 5 is based on Example 3. The difference between Example 5 and Example 3 is that in Example 5, 19.33 g of citronella essential oil, 6.67 g of emulsifier and 4 g of nano silver particles are used in preparing the antibacterial microcapsules.

[0046] Example 6 Example 6 is based on Example 3, but no nanosilver particles are added when preparing the antibacterial microcapsules.

[0047] Example 7 Example 7 is based on Example 3. The difference between Example 7 and Example 3 is that in Example 7, 30 g of methyltrimethoxysilane and 10 g of dimethyldimethoxysilane are used in preparing the silica aerogel material.

[0048] Example 8 Example 8 is based on Example 3. The difference between Example 8 and Example 3 is that in Example 8, 33.33 g of methyltrimethoxysilane and 6.67 g of dimethyldimethoxysilane are used in preparing the silica aerogel material.

[0049] Example 9 Example 9 is based on Example 3. The difference between Example 9 and Example 3 is that in Example 10, 0.3 g of γ-aminopropyltriethoxysilane is used when preparing the modified aerogel system.

[0050] Example 10 Example 10 is based on Example 3. The difference between Example 10 and Example 3 is that in Example 10, 1.8 g of γ-aminopropyltriethoxysilane is used in preparing the modified aerogel system.

[0051] Embodiment 11 Example 11 is based on Example 3. The difference between Example 11 and Example 3 is that in Example 11, when preparing the silica aerogel material, the amount of hexadecyltrimethylammonium bromide used is 0.1 g.

[0052] Example 12 Example 12 is based on Example 3. The difference between Example 12 and Example 3 is that in Example 12, when preparing the silica aerogel material, the amount of hexadecyltrimethylammonium bromide used is 0.4 g.

[0053] Embodiment 13 Example 13 is based on Example 3. The difference between Example 13 and Example 3 is that in Example 13, when preparing the silica aerogel material, the amount of ammonia water used is 1 mL.

[0054] Embodiment 14 Example 14 is based on Example 3. The difference between Example 14 and Example 3 is that in Example 14, when preparing the silica aerogel material, the amount of ammonia water used is 4 mL.

[0055] Comparative Example 1 Comparative Example 1 is based on Example 3, and in Comparative Example 1, the silica aerogel is replaced by ordinary nano-silicon dioxide.

[0056] Comparative Example 2 Comparative Example 2 is based on Example 3, but in Comparative Example 2, γ-aminopropyltriethoxysilane is not used to treat the silica aerogel material.

[0057] Comparative Example 3 Comparative Example 3 is based on Example 3, and in Comparative Example 3, the antibacterial microcapsules are replaced with an equal amount of citronella essential oil.

[0058] Performance testing The following performance tests were performed on the samples of Examples 1-15 and Comparative Examples 1-3: (1) Thermal insulation performance test The thermal insulation rate of the samples was tested according to GB / T 11048-2008. Each sample was tested three times, the average value was taken, and the test results were filled in Table 1.

[0059] (2) Antibacterial performance test Taking “GB / T 20944.1 Evaluation of antibacterial properties of textiles” as the testing standard, the antibacterial performance of the prepared fabrics was tested, and the antibacterial rate was tested after 7d and 120d respectively. Each sample was tested 3 times, and the average value was taken. The test results were filled in Table 1.

[0060] (3) Hydrophobicity test The contact angle of the sample surface was tested. Each sample was randomly tested three times, and the average value was taken. The test results were filled in Table 1.

[0061] Table 1 Test results of samples of Examples 1-15 and Comparative Examples 1-3 Data analysis Combined with Table 1, it can be seen that the warmth retention rates of Examples 1-3 are all 58% or more, indicating that the thermal insulation fiber prepared in the present application has good thermal insulation performance; the antibacterial rates of Escherichia coli in Examples 1-3 after 3 days are all 99.66% or more, and the antibacterial rates of Staphylococcus aureus are all 77.92% or more, indicating that the fiber prepared in the present application has good antibacterial performance, the antibacterial rates of Escherichia coli in Examples 1-3 after 28 days are all 96.18% or more, and the antibacterial rates of Staphylococcus aureus are all 96.02% or more, indicating that the fiber prepared in the present application has long-lasting antibacterial performance, and the hydrophobic angles of Examples 1-3 are all 132° or more, indicating that the fiber prepared in the present application has good hydrophobic performance.

[0062] In the preparation of antibacterial microcapsules in Examples 4 and 5, the mass ratios of citronella essential oil, emulsifier and nano-silver particles are not within the range defined in the present application. When the content of citronella essential oil is too little, the particle size of the formed microcapsules is too small and agglomerates, making it difficult to disperse evenly in the system, and the stability decreases. When the content of citronella essential oil is too much, the latex micelles formed during the emulsification process become larger, the particle size uniformity is different, and the stability of the system decreases. Therefore, the performance of Examples 4 and 5 is reduced.

[0063] In Example 6, nanosilver is replaced with methyl methacrylate when preparing antibacterial microcapsules. Methyl methacrylate does not have antibacterial properties and is difficult to synergize with citronella essential oil to improve the antibacterial properties of the system. The antibacterial properties are poor in the initial stage and will also affect the subsequent antibacterial effects. At the same time, the thermal stability of methyl methacrylate is poorer than that of nanosilver particles, so the thermal insulation performance is also affected.

[0064] In Example 7 and Example 8, when preparing the silica aerogel material, the mass ratio of methyltrimethoxysilane to dimethyldimethoxysilane was adjusted. When the content of methyltrimethoxysilane was too little, the hydrophobicity of the precursor in the water-in-oil emulsion droplets was too strong, and the stability of the emulsion system formed by being wrapped by hexadecyltrimethylammonium bromide decreased, resulting in a decrease in the particle size uniformity of the silica aerogel material, affecting the overall stability of the system; when the content of methyltrimethoxysilane was too much, the hydrophobicity decreased too quickly, and it was gradually difficult to be coated by hexadecyltrimethylammonium bromide to form a stable emulsion system, thereby causing some of the aerogel microspheres to adhere, resulting in a large number of irregular products, affecting the uniformity and stability of the system.

[0065] In Example 9 and Example 10, when preparing the modified aerogel system, the content of γ-aminopropyltriethoxysilane used is not within the range specified in the present application. When the content of γ-aminopropyltriethoxysilane is too little, the modification effect on the surface of the silica aerogel material is weak, and the dispersion effect is difficult to be further improved; when the content of γ-aminopropyltriethoxysilane is too much, the stability of the silica aerogel is affected.

[0066] When preparing the silica aerogel material, when the amount of hexadecyltrimethylammonium bromide used is too small, the silica aerogel microspheres adhere to each other, and the uniformity and dispersibility of the system are reduced; when the amount of hexadecyltrimethylammonium bromide used is too large, the particle size of the water-in-oil emulsion droplets in the system is further reduced, it is difficult to exist stably, and adhesion occurs again, so the performance of Example 11 and Example 12 are both reduced.

[0067] When preparing silica aerogel material, ammonia water as a catalyst affects the dispersibility of silica aerogel. When the amount of ammonia water used is too little or too much, the silica aerogel will adhere, thereby reducing the stability. Therefore, the performance of Example 13 and Example 14 are both reduced.

[0068] In Comparative Example 1, the silica aerogel is replaced with common nano-silica particles. It is difficult to obtain a large number of nano-pores with common silica particles, and the thermal insulation performance is reduced, and the hydrophobicity is also reduced.

[0069] In Comparative Example 2, the silica aerogel material was not subjected to surface modification treatment with γ-aminopropyltriethoxysilane, and the compatibility and dispersibility of the unmodified silica aerogel material in the system were difficult to improve, which affected the overall stability of the system.

[0070] In Comparative Example 3, the antibacterial microcapsules were replaced with citronella essential oil. The citronella essential oil without shell material protection only had certain antibacterial properties in the early stage, but rapidly inactivated in the later stage, making it difficult to achieve a long-term antibacterial effect.

[0071] This specific embodiment is only an explanation of the present application, and it is not a limitation of the present application. Through the above description, relevant staff can make various changes and modifications without deviating from the technical idea of ​​the present application. The technical scope of the present application is not limited to the content in the specification, and its technical scope must be determined according to the scope of the claims.

Claims

1. A thermal insulation fiber, characterized in that: It comprises a fiber body and a heat-insulating coating, wherein the heat-insulating coating is obtained by coating the heat-insulating coating on the surface of the fiber body, and the heat-insulating coating comprises a modified aerogel system, an antibacterial microcapsule system, an aqueous polyurethane and a dispersant; The modified aerogel system comprises a silicon dioxide aerogel material and a silane coupling agent.

2. The thermal insulation fiber according to claim 1, characterized in that: The silica aerogel material is prepared by the following method: Hexadecyltrimethylammonium bromide is mixed with water, and then methyltrimethoxysilane is added, and the mixture is stirred until the system is formed to obtain an oil-in-water emulsion. After hydrolysis, dimethyldimethoxysilane is added to continue hydrolysis to obtain a dispersion. Span-80 is added to n-hexane, and the above dispersion is added to obtain a mixed solution. The mixed solution is stirred to condense a gel, and the gel is separated after filtration, washed, immersed in the mixed solution for aging, and then filtered and dried, and ground to obtain a silica aerogel material.

3. The thermal insulation fiber according to claim 2, characterized in that: The mass ratio of the methyltrimethoxysilane to the dimethyldimethoxysilane is (3.4-3.8):

1.

4. The thermal insulation fiber according to claim 1, characterized in that: The modified aerogel system is prepared by the following method: after mixing γ-aminopropyltriethoxysilane, ethanol and water, ultrasonically obtaining a silane coupling agent solution, adding a silica aerogel material into the silane coupling agent solution and ultrasonically obtaining the modified aerogel system after drying and grinding.

5. The thermal insulation fiber according to claim 4, characterized in that: The silane coupling agent includes γ-aminopropyltriethoxysilane.

6. The thermal insulation fiber according to claim 5, characterized in that: The mass ratio between the silica aerogel material and the silane coupling agent is 1:(0.02-0.04).

7. The thermal insulation fiber according to claim 1, characterized in that: The antibacterial microcapsule system comprises nano silver particles, citronella essential oil and an emulsifier.

8. The thermal insulation fiber according to claim 7, characterized in that: The antibacterial microcapsule system is prepared by the following method: The nanosilver particles are mixed with water, and a nanosilver ion suspension is obtained after ultrasound. The nanosilver particle suspension is mixed with an emulsifier to obtain a nanosilver particle mixture. Citronella essential oil, methyl methacrylate, ethoxylated trimethylolpropane triacrylate, and azobisisobutyronitrile are mixed to obtain an oil phase. The oil phase is mixed with the nanosilver particle mixture and stirred. The temperature is raised and the stirring is maintained for polymerization reaction for 8 hours to obtain antibacterial microcapsules.

9. The thermal insulation fiber according to claim 8, characterized in that: The mass ratio of the citronella essential oil, the emulsifier and the nano-silver particles is (1.2-1.6):1:0.

6.

10. A textile made of thermal insulation fiber, characterized in that: The thermal insulation fiber is prepared from any one of claims 1 to 9.